Draft Genome Sequences of 29 Helicobacter pylori Strains Isolated from Colombia - Muñoz, Angela B. (2022)
Here, we present the draft genome sequences of 29 Colombian Helicobacter pylori strains. These strains were isolated in Bogotá, Colombia, from patients diagnosed with chronic gastritis. The genomic characterization of these strains will provide more information on the genetic composition of H. pylori strains from Colombia.